2022
DOI: 10.18006/2022.10(1).211.226
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Artificial Intelligence in Healthcare

Abstract: Now in these days, artificial intelligence (AI) is playing a major role in healthcare. It has many applications in diagnosis, robotic surgeries, and research, powered by the growing availability of healthcare facts and brisk improvement of analytical techniques. AI is launched in such a way that it has similar knowledge as a human but is more efficient. A robot has the same expertise as a surgeon; even if it takes a longer time for surgery, its sutures, precision, and uniformity are far better than the surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that these controllers can outperform traditional model-based controllers, particularly when used with challenging-to-model nonlinear systems. There are four main components that make up the FLC configuration at its core [71,72]:…”
Section: Robotic Process Automationmentioning
confidence: 99%
“…It has been demonstrated that these controllers can outperform traditional model-based controllers, particularly when used with challenging-to-model nonlinear systems. There are four main components that make up the FLC configuration at its core [71,72]:…”
Section: Robotic Process Automationmentioning
confidence: 99%
“…They are now used in clinical settings to help healthcare workers and patients. For instance, hospitals and clinics are deploying robots for various tasks to help reduce pathogen exposure during the COVID-19 pandemic [9].…”
Section: Healthcare Fieldmentioning
confidence: 99%
“…In subsequent years, accuracy in classifying pulmonary nodules has increased to 95.3% using unlabeled C.T. (Quazi et al 2022).…”
Section: Predicting Lung Diseases Via DL Modelsmentioning
confidence: 99%